Violence is Islam, Violence is Not Islam: Meaning-Making Among Muslim Men in Norway - Ahmed, Uzair (The British journal of criminology, 2024)
This article employs cultural repertoire theory to investigate how 84 Muslim men in Norway make meaning of adopting or rejecting political violence. Previous studies have addressed political violence among Muslims, but little attention has been paid to how its adoption and rejection involve self-ascription and ascriptions by others. The participants made meaning by drawing on stories about their past, exclusion and belonging, in addition to religious worldviews and political knowledge, including boundaries of class, crime, violence, race, religion and gender. Muslims are informed by mainstream ascriptions of them as extreme others and inherently radicalized in their meaning-making. This finding has important implications for how Muslim radicalization should be understood and countered.